PENGEMBANGAN WEBSITE DAN MEDIA SOSIAL SEBAGAI UPAYA PENINGKATAN PEMASARAN DESA WISATA BEDULU - Putra, Kadek Andika Astina; Paramitha, A A Istri Ita; Putra, I Gede Eka Juliana (LPPM Universitas Flores, 2024)
The recovery of Bali's tourism post-COVID-19 has shifted the trend from mass tourism to alternative tourism, benefiting tourist villages such as Bedulu Tourist Village. However, promoting the village's potential was hindered by the inactivity of previously used websites and social media. A digital village acceleration program was implemented through the collaboration between the Gianyar Community and Village Empowerment Office and Bedulu Village, alongside Primakara University. This program involved the development of a website and social media to enhance the marketing of Bedulu Tourist Village, running for six months from November 2023 to April 2024. The implementation method included preparation, needs analysis, data collection, website and social media development, and village staff training on website management. As a result, the website is ready to be launched upon hosting funding, and promotional content has been successfully uploaded and reposted by media accounts. Evaluations indicate that Bedulu Village's staff can effectively manage both social media and the website. Thus, this development initiative supports the marketing efforts of Bedulu Tourist Village and demonstrates an improvement in the village staff's technological management skills.